Implementasi Penjaminan Mutu dan Performnasi Kerja di Pondok Pesantren Modern Asy-Syifa Balikapapan - Kartika fitrin (FENOMENA, 2021)
Quality assurance in education institution, particularly in the Asy-Syifa Balikpapan, which its owner can see directly. The modern boarding house employs a quality assurance system aimed at generating output that is able to compete with schools in general, so to speak. Because asy-shifa ponpes are able to synergize toward the progress of this cottage itself. As for the performance of the performance of teachers in the ponpes, they perform performance to provide a good service in the field of service and learning to achieve a quality education and to meet established standards. This paper aims to know how to apply quality assurance and performation at modern boarding hut asy-shifa balickboard using a qualitative approach through descretive methods. The result of this study was to see the application of quality assurance and performance performance applied to the modern cottage of asy-shifa balikpapan.